(untitled) (Dhaka University Journal of Biological Sciences, 2015)
The quantitative analysis of A. lumbricoides eggs in stool of 205 subjects (male 101 and female 104) showed that the mean eggs per gram(EPG) by Kato‐ Katz (KK) (EPG = 11130.89) was markedly higher than those of Formal‐Ether concentration technique (FE) (EPG = 1593.32). Co‐efficient of correlation was significant (r = 0.453**) at p = 0.01 level. Age based comparison among the subjects also revealed that KK had a better quantification of A. lumbricoides eggs than FE. Dhaka Univ. J. Biol. Sci. 24(1): 65-72, 2015 (January)